Developing a methodology to quantify mismanaged plastic waste entering the ocean in coastal countries. (16th December 2022) - Ita‐Nagy, Diana; Vázquez‐Rowe, Ian; Kahhat, Ramzy
Abstract: Marine plastic accumulation has gained international attention in recent years. Sources, pathways, and environmental impacts are being currently studied to understand the complex interactions during waste, especially plastic, transportation to the sea. Rivers have been identified as debris corridors allowing transportation of mismanaged waste. However, there is also evidence of waste accumulation in river basins, suggesting they can also act as sinks. Thus, assuming a uniform and continuous transportation of waste through rivers towards the ocean may signify an oversimplification. This study proposes a methodology to estimate plastic release to the ocean, considering a more detailed characterization of each river basin, including natural attributes and manmade constructions that may act as barriers or boosters for this release. The methodology is exemplified using a case study for the Region of Piura, Peru, and estimating a range of 4.2 to 13.9 kg/person/year of plastic waste reaching the Pacific coast during 2018. These results, when compared with the existing literature, demonstrate more conservative estimations. This methodology is presented as a useful tool that can be easily applied to develop more accurate mismanaged waste dissipation along different compartments.